PROPHYLAXIS CAUSED BY OVERLOADING THE JUNIOR JUDO PLAYER (GYMNASIUM, 2017)
The research was conducted on judo performance, from the National Romanian Olympic Junior Judo Centre from Pitesti. In the first phase subjects we discussed and insisted on postural defects awareness and adoption of hypercorrection posts. In the second phase begins corrective physical therapy programs, aimed at toning the muscles of the back and seat scapula-humeral and pelvic muscle tone and movement promoting linkages within. In the first category 14 athletes have incorrect postural attitudes to an improvement in their clinical symptoms. For the other four programs should continue for months or years to obtain the necessary correction. 90% of subjects studied had attitudes among kyphotic, kyphoscoliosis, scoliosis, and inadequacies kyphosis and scoliosis. By implementing physical therapy programs we followed the following objectives: enhancing the mobility of the spine; Postural recovery; Selective muscle tone back and abdomen; paravertebral muscles change length selection; improving respiratory function; general training body.